2018
DOI: 10.5336/medsci.2018-60404
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Vitiligo with Insulin Resistance and Metabolic Syndrome

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu çalışmada vitiligo ile insülin direnci ve metabolik sendrom (MetS) arasındaki ilişkinin araştırılması amaçlandı. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Prospektif, gözlemsel vaka-kontrol çalışması olarak planlanmış olan araştırmamıza vitiligo tanısı ile takip edilmekte olan 40 hasta ve hastalar ile yaş ve cinsiyet bakımından benzer 23 sağlıklı kontrol dahil edildi. Açlık kan örneklerinden; glukoz, insülin, C-peptit düzeyleri ve lipid profilleri çalışıldı. İnsülin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Onan et al found remarkably higher levels of insulin and triglyceride levels in patients with vitiligo. However, no significant increase was found in the prevalence of insulin resistance or metabolic syndrome in their study [30]. Increased prevalence of vitiligo in type 2 diabetes patients has also been seen in some studies [31,32].…”
Section: Clinical Outcomesmentioning
confidence: 74%
“…Onan et al found remarkably higher levels of insulin and triglyceride levels in patients with vitiligo. However, no significant increase was found in the prevalence of insulin resistance or metabolic syndrome in their study [30]. Increased prevalence of vitiligo in type 2 diabetes patients has also been seen in some studies [31,32].…”
Section: Clinical Outcomesmentioning
confidence: 74%